A review of the Gordiacea (Nematomorpha) in the collection of the California Academy of Sciences with the description of a new species - Bellusci de Miralles, Delma A. (1995)
The Gordiacea of the California Academy of Sciences collection are studied. The specimens are included in the known species Gordius robustus Leidy, Pseudochordodes bedriagae (Camerano) and a new species, Neochordodes californensis n. sp. is proposed. Morphological, morphometric and geographical data are provided for these species.